Single and Split Herbicide Applications for Efficacy in Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to compare season-long weed control from single and sequential herbicide applications in corn. Control of all weed species was generally good (90% or more) early in the season regardless of preemergence (PRE) herbicide. However, Russian thistle and Palmer amaranth control was best later in the season when a PRE herbicide was followed by a postemergence (POST) treatment. While all herbicide treatments increased yields compared to the untreated control, yields were greatest when Lumax EZ PRE (atrazine/mesotrione/metolachlor) was followed by Acuron (atrazine/bicyclopyrone/mesotrione/metolachlor) and glyphosate POST.
Keywords: Sequential applications; residual control; herbicide; corn